ANALYSIS OF KARTINIPEDIA APPLICATION INVESTMENT OPPORTUNITIES USING NET PRESENT VALUE - Shinta Kumala Dwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The internet connects people all over the world, taking advantage of this business opportunity, one of which is information-based e-commerce. The concept of shopping is now developing as a lifestyle and a fun activity, especially for women. Not only shopping, women also need information and a comfortable space to share. Kartinipedia: Center for Women's Needs and E-Commerce Android-based applications are a new breakthrough as a solution for women to get both in just one application. This study uses an approach based on literature analysis of the NPV approach. This article is for innovative performance measurement issues. It focuses on techniques that can be used for the evaluation of a single innovation project. This technique can guide a value innovation project by providing an indication of its financial potential.